Sleep quality in Noisy Aircraft Cabins - Sieben, N.R.; Maij, A.; Zon, G.D.R.; Aalmoes, R.; Marsman, L.A.; Drongelen, A. van (Comfort Congress, 2023)
This exploratory study has investigated the effects of cabin noise on passenger sleep length and quality, because the influence of cabin comfort and particularly cabin noise levels on sleep length and quality is not yet fully understood. Therefore, a feasibility study was conducted to explore the possibilities for a more extensive laboratory sleep study that will be executed later. In this feasibility study two groups of four ‘passengers’ slept under different circumstances. To simulate an immersive experience, these ‘passengers’ were seated on real aircraft chairs and slept in a semi-noise-controlled environment. Each group faced different variances of cabin noise loudness. The effects of these different conditions on sleep length, quality and comfort levels were measured and compared with each other, and with a control condition where subjects slept in their own bed at home. Demographic factors and general sleep quality were gathered to account for individual differences. The results show that sleeping in the own bed at home is related to better sleep quality and less subsequent fatigue. However, no significant results on sleep and fatigue were found between the different noise conditions